ORAL MANIFESTATIONS AND INJURIES RELATED TO COVID-19: AN EXPERIENCE REPORT ON THE ROLE OF HOSPITAL DENTISTRY - Pedack , Francis Rossetti; Rosa, Marciano Eduardo da; Stall , Jaqueline; Coelho, Karina Munhoz de Paula Alves; França , Paulo Henrique Condeixa de; Gonçalves, Jussara Maria (Arquivos de Ciências da Saúde da UNIPAR, 2023)
SARS-COV-2 is transmitted among human beings by saliva droplets that come in direct contact with the oral cavity, nose, and eyes. Since the mouth is one of the anatomical sites primarily contaminated, oral manifestations have also been reported beyond the serious consequences inherent to progressive respiratory failure. This study aimed to identify oral manifestations possibly related to the infection by COVID-19 in hospitalized patients. A prospective study was carried out with patients diagnosed with COVID-19 in the period between March and June 2021, admitted to the Moderate COVID-19 Care Unit of the Hans Dieter Schmidt Regional Hospital, by applying a form and performing a clinical exam of the oral cavity. Out of all patients (n=45), 33.3% reported both olfactory (anosmia) and taste dysfunction (dysgeusia), with an average duration of 5.9 ±3.0 days. Regarding other oral manifestations evaluated, two patients reported dry and burning mouth and one patient reported a change in taste associated with plaque-like changes in the tongue. No patients presented ulcers or other lesions in the oral cavity. Olfactory and taste dysfunction were symptoms recognized of the novel coronavirus disease (COVID-19). However, the association with other oral manifestations is still controversy. Unfortunately, dentistry professionals are still not part of most teams in the hospital environment, mostly because of the lack of prioritization of dental care. Working with a multidisciplinary team may avoid possible systemic complications due to poor dental care.